2018
DOI: 10.3389/fpls.2018.00241
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Phenolic Profiling: A New Selection Criterion in Olive Breeding Programs

Abstract: Olive growing is mainly based on traditional varieties selected by the growers across the centuries. The few attempts so far reported to obtain new varieties by systematic breeding have been mainly focused on improving the olive adaptation to different growing systems, the productivity and the oil content. However, the improvement of oil quality has rarely been considered as selection criterion and only in the latter stages of the breeding programs. Due to their health promoting and organoleptic properties, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 44 publications
(79 reference statements)
9
34
1
Order By: Relevance
“…Response factors were calculated for each phenolic compound. Identification of compounds was confirmed by HPLC/ESI-qTOF-HRMS on a liquid chromatograph Dionex Ultimate 3000 RS U-HPLC liquid chromatograph system (Thermo Fisher Scientific, Waltham, MA, USA) equipped with a similar column and elution program [33]. Mass spectra were acquired in MS fullscan mode and data were processed using TargetAnalysis 1.2 software (Bruker Daltonics, Bremen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Response factors were calculated for each phenolic compound. Identification of compounds was confirmed by HPLC/ESI-qTOF-HRMS on a liquid chromatograph Dionex Ultimate 3000 RS U-HPLC liquid chromatograph system (Thermo Fisher Scientific, Waltham, MA, USA) equipped with a similar column and elution program [33]. Mass spectra were acquired in MS fullscan mode and data were processed using TargetAnalysis 1.2 software (Bruker Daltonics, Bremen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…To do this, cultivars may be selected from the vast genetic pool that already exist or may be generated from the crossing of cultivars that are characterized by exhibiting a particular phenotype. Thus, in addition to traditional agronomic traits [18], the functional quality of VOO has been considered lately as a target of breeding programs that aim to obtain new olive cultivars [19,20,21]. With this in mind, the purpose of the present research was to conduct a study of the vitamin E content in olive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that domestication of olive was driven by gene expression, rather than genomic changes (Gros-Balthazard et al, 2019). It has also been reported that secoiridoid contents are mainly controlled by the cultivar genotype (Miho et al, 2018;Pérez et al, 2018;Deiana et al, 2019). Notably, published transcriptomic datasets for olive have shown that OeOMES expression is not substantially increased by environmental stresses, but is more highly expressed in domesticated versus wild olives.…”
Section: Discussionmentioning
confidence: 90%
“…Obtaining olive varieties with "fine-tuned" oleuropein levels is an important goal of olive breeding programs (Pérez et al, 2018). The benefits of secoiridoid-related markers have been recently highlighted in the industrial processing of table olives, where oleuropein degradation via glucosidases was a major biochemical marker for strain selection (Bavaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation